Isotopic Geochronological Constraints on the Formation and Evolution of the Moon - Ai-Cheng Zhang; Huai-Yu He; Sen Hu; Xian-Hua Li; Yang-Ting Lin; Li-Ping Qin; Gui-Qin Wang; Zhi-Yong Xiao (Space: Science & Technology, 2024)
One major task of studying the formation and evolution of the Moon is to construct a timeline of the important events with precise isotopic ages. Here, we review recent major isotopic geochronological progress in the past decade and the unsolved problems in isotopic geochronology. The Moon probably formed between 4.52 and 4.42 Ga. Recent high-precision whole-rock and mineral Sm-Nd isotopic dating results suggested that ferroan anorthosite and highlands magnesian suite rocks formed contemporarily around 4.37 to 4.33 Ga. Although the major mare basaltic volcanism took place from 3.85 to 2.93 Ga, new geochronological data from lunar meteorites and Chang’e-5 basalts suggested that lunar basaltic volcanism took place as old as up to 4.37 Ga and at least as young as 2.0 Ga, respectively. Impact events older than 3.9 Ga have also been revealed based on U-bearing minerals Pb/Pb ages and Ar-Ar ages and can provide important clues to understand the late heavy bombardment hypothesis. However, the reliable isotopic ages for the important events on the Moon are still far from conclusive, due to lack of pristine samples that directly crystallized from Lunar Magma Ocean and samples from impact melt sheets in large impact basins (e.g., the South Pole-Aitken basin). In the future, collection and return of pristine samples of ferroan anorthosite and highlands magnesian suite rocks from the farside, cryptomare basalts and late-stage basalts, quartz monzogabbros, granites/felsites, and rocks from impact melt sheets in large impact basins are required for better understanding the formation and evolution of the Moon.